2015
DOI: 10.1038/srep09918
|View full text |Cite|
|
Sign up to set email alerts
|

Recombinant Mutated Human TNF in Combination with Chemotherapy for Stage IIIB/IV Non-Small Cell Lung Cancer: A Randomized, Phase III Study

Abstract: Tumor necrosis factor (TNF), an anti-angiogenic agent in cancer treatment, is limited to isolated limb perfusion due to systemic toxicities. We previously prepared a TNF mutant (rmhTNF) that significantly improved responses in lung cancer patients and exhibited a promising safety profile in phase I and II studies. To further investigate whether rmhTNF with standard chemotherapy provides a survival benefit, 529 patients with stage IIIB/IV non-small cell lung cancer (NSCLC) were randomly assigned to receive doce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…An in-depth analysis of the chemotactic mechanisms attracting circulating fibrocytes to the lung cancer microenvironment was not the major focus of the present study, although inflammatory cytokines such as IL-2, TNFα and CXCR4 are implicated in fibrocyte recruitment under different disease conditions 32 – 35 . This is consistent with preceding observations from our own and other groups that markedly increased levels of cytokines, including IL-2, TNFα and CXCR4, are detected in experimental and human lung cancer tissue 19 , 24 , 36 38 . van Deventer et al reported that fibrocytes predispose the lung to B16-F10 metastasis by recruiting Ly-6C (+) monocytes 16 .…”
Section: Discussionsupporting
confidence: 94%
“…An in-depth analysis of the chemotactic mechanisms attracting circulating fibrocytes to the lung cancer microenvironment was not the major focus of the present study, although inflammatory cytokines such as IL-2, TNFα and CXCR4 are implicated in fibrocyte recruitment under different disease conditions 32 – 35 . This is consistent with preceding observations from our own and other groups that markedly increased levels of cytokines, including IL-2, TNFα and CXCR4, are detected in experimental and human lung cancer tissue 19 , 24 , 36 38 . van Deventer et al reported that fibrocytes predispose the lung to B16-F10 metastasis by recruiting Ly-6C (+) monocytes 16 .…”
Section: Discussionsupporting
confidence: 94%
“…Our results suggest that our approach is capable of directly monitoring delivery of nanoparticulate chemotherapeutics. Moreover, as TNF-α is being investigated clinically for improving the drug delivery of chemotherapy [ 26 ], this approach may also be useful for assessing the tumor responses to the combination of nanomedicine and TNF-α or other vascular-targeting treatment.…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α is a pro-inflammatory cytokine that is cytotoxic for tumor cells. It has been demonstrated that increased TNF-α levels in NSCLC correlate with improved outcomes, while TNF mutants have been proposed as anticancer chemotherapeutic drugs [ 61 , 62 ]. This dichotomous result in terms of antitumor immunity profiling could suggest a deregulation of the innate immunity mechanisms early on in the inflammasome process.…”
Section: Discussionmentioning
confidence: 99%